2022
DOI: 10.1186/s13006-022-00457-w
|View full text |Cite
|
Sign up to set email alerts
|

The visibility of breastfeeding as a sexual and reproductive health right: a review of the relevant literature

Abstract: Background Governments must protect and apply maximum feasible resourcing to the protection, promotion and support of breastfeeding in order to meet their international legal obligations with respect to the human rights of women and children. However, governments across the world have consistently failed in these duties. Breastfeeding has been notably absent from mainstream feminist advocacy on sexual and reproductive health rights (‘SRH rights’). Why is there this lack of focus on breastfeedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The study also reveals that "..meaningful discussion of breastfeeding is overwhelmingly absent from the sexual and reproductive health rights literature..". Moreover, align with Galtry, Stone and Smith assert that discussions concerning breastfeeding have given much weight to children's right to health (Stone and Smith, 2022). Prioritizing infant's right to be breastfed over mother's right of autonomy would certainly affects the appreciation to the later.…”
Section: Literature Review Theoretical Backgroundmentioning
confidence: 95%
See 2 more Smart Citations
“…The study also reveals that "..meaningful discussion of breastfeeding is overwhelmingly absent from the sexual and reproductive health rights literature..". Moreover, align with Galtry, Stone and Smith assert that discussions concerning breastfeeding have given much weight to children's right to health (Stone and Smith, 2022). Prioritizing infant's right to be breastfed over mother's right of autonomy would certainly affects the appreciation to the later.…”
Section: Literature Review Theoretical Backgroundmentioning
confidence: 95%
“…Discussions elaborating breastfeeding under the sphere of mother's sexual and reproductive rights is trifling. Study by Stone and Smith upon 87 publications which are English written, published in 2003 and afterwards, collected mostly from online databases such as ScienceDirect, SagePub, JSTOR, ProQuest and Google Scholar, with some exemptions, found that more than 70 percent of the publications do not refer or discuss about breastfeeding (Stone and Smith, 2022). The study also reveals that "..meaningful discussion of breastfeeding is overwhelmingly absent from the sexual and reproductive health rights literature..".…”
Section: Literature Review Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Breastfeeding is initiated with the child first suckling at the breast and may continue for some years. Pregnancy, birth, and breastfeeding form a reproductive continuum and breastfeeding is a biological process that has reproductive health implications and reproductive rights associated with it ( 38 , 50 , 51 ). However, breastfeeding is both a biological and social phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016 UN Human Rights Agencies reinforced women’s human rights on breastfeeding, including to be fully enabled to breastfeed such as by BFHI implementation, of adequate maternity care, and comprehensive implementation of the International Code of Marketing of Breastmilk Substitutes in all countries to protect informed decision-making. A recent review indicates that there is poor awareness of women’s human rights regarding breastfeeding in women’s sexual and reproductive rights literature, although children’s rights are better known [ 14 ].…”
Section: Introductionmentioning
confidence: 99%